Enhanced Healing and Bone re-Modelling by Low-Level Laser Therapy for Rapid Pain Control in Pediatric Fractures - David, Ip (International Journal of Pain Management, 2019)
Objective The current clinical case series assess the clinical outcome of the use of low-level laser in the treatment of painful pediatric fractures not solidly consolidated and re-modelled after casting for a standard of 4-6 weeks Materials and Methods The patient cohort consisted of 17 consecutive unselected patients in pediatric age group with delayed fracture consolidation and/or undesirable angulation despite casting for a standard period of 4-6 weeks in whom the parents refused any surgical intervention and/or bone grafting options. All subjects were referred from other medical centers after inadequate healing of the fracture ends upon repeating the x ray after the cast was off at the 4-6 weeks mark. Low-level laser therapy (LLLT) on alternate days for 8weeks in upper limb fracture cases, and 12 weeks in lower limb fracture cases were administered with a view of enhancing bone healing and/or re-modelling since both previous clinical and basic science studies on LLLT showed a stimulatory effect on fracture healing. Results All patients had solid union, mean time for union for upper and lower limb fractures were 6 and 10 weeks respectively. The calculated p value is statistically significant at p < 0.05. No patient defaulted follow up. All parents were satisfied with the clinical and radiological result of the LLLT treatment. Conclusion LLLT was found not only to enhance bone healing potential but in fact improved bone re-modelling when used in the proper wavelength and energy density in pediatric upper and lower limbs fractures, thereby also rapidly resolve the intolerable pain in paediatric fracture population
Keywords: Low-level laser therapy; fracture; limb fractures.